Culture and the Translation of Self-Help Discourse - Sabry, Reem (2012)
A Master of Arts Thesis in Translation and Interpreting (English/Arabic/English) by Reem Sabry entitled, "Culture and the Translation of Self-Help Discourse." Thesis advisor is Dr. Said Faiq and was submitted in December 2012. Available are both hard and soft copies of the thesis.